Generalized syringoma: benign, yet a serious cosmetic problem - Marahatta, Suchana; Upadhayay, Paricha; Yadav, Ramgyan (Journal of Chitwan Medical College, 2017)
Syringoma is a benign appendageal neoplasm of the eccrine ducts. The word “Syringoma” has been derived from greek word “Syrinx”, meaning pipe of tube. Friedman & Butler has classified it into four principal clinical variants. Among them, generalized syringoma is a rare variant comprising two sub-varients: multiple syringoma and eruptive syringoma. It presents with multiple crops of skin colored to tan colored, flat topped papules of 1-3 mm diameter, distributed symmetrically over face, trunk and extrimities. It is a benign disease with great cosmetic concern.